Suppression of multiple ion bunches and generation of monoenergetic ion beams in laser foil-plasma - 张闪 谢柏松 洪学仁 吴海城 艾米尔丁·艾米都拉 赵学燕 刘明萍 (Chinese physics B, 2011)
In one-dimensional particle-in-cell simulations, this paper shows that the formation of multiple ion bunches is disadvantageous to the generation of monoenergetic ion beams and can be suppressed by choosing an optimum target thickness in the radiation pressure acceleration mechanism by a circularly polarised laser pulse. As the laser pulse becomes intense, the optimum target thickness obtained by a non-relativistic treatment is no longer adequate. Considering the relativistic Doppler-shifted pressure, it proposes a relativistic formulation to determine the optimum target thickness. The theoretical predictions agree with the simulation results well. The model is also valid for two-dimensional cases. The accelerated ion beams can be compelled to be more stable by choosing the optimum target thickness when they exhibit some unstable behaviours.